Engineers - Hart-Davis, Adam (Dorling Kindersley Limited, 2017)
Full of incredible tales of achievement and ingenuity, Engineers celebrates the greatest engineers that ever lived and the stamp they have left on our world. Learn all about how engineering projects have changed the course of history and added to human progress, from those who built the Great Pyramid in Egypt to the Industrial Revolution and beyond.